Benthic Foraminifera from the Capricorn Group, Great Barrier Reef, Australia - Mamo, Briony L. (Zootaxa, 2016)
Effective reef management and monitoring has become increasingly important as anthropogenic processes impact upon natural ecosystems. One locality that is under direct threat due to human activities is the Australian Great Barrier Reef (GBR). Marine foraminifera represent an abundant and readily applicable tool that can be used in reef studies to investigate a variety of ecological parameters and assist in understanding reef dynamics and influence management protocols. The first step is to establish a baseline knowledge of taxonomic composition within the region to facilitate comparative studies and monitor how assemblages change in order to maximise effective management. A detailed taxonomic assessment is provided of 133 species of benthic foraminifera in 76 genera from Heron Island, One Tree Island, Wistari and Sykes Reefs, which form the core of the Capricorn Group (CG) at the southern end of the GBR. Of these 133 species, 46% belong to the order Miliolida, 34% to Rotaliida, 7% to Textulariida, 5% to Lagenida, 3% to Lituolida, 3% to Spirillinida, 1% to Loftusiida and 1% to Robertinida. Samples were collected from a variety of shallow shelf reef environments including reef flat, lagoonal and channel environments. Seventy species, representing the most abundant forms, are formally described with detailed distribution data for the remaining 63 species supplied.